PERKEMBANGAN FUNGSI DAN BENTUK TARI ZAPIN ARAB DI KOTA PALEMBANG (1991-2014) - N. Nurdin (Gelar : Jurnal Seni Budaya, 2014)
The research discusses about the development of the function and form of dance Zapin Arab in Palembangcity (1991-2014), through the qualitative approach (the research is qualitative, what is the approach? It issociology, anthropology, history or others). The data is collected by the method of observation, depth interview,and library study. The data is analyzed descriptively and qualitatively, and the data validity is tested bytriangulation method. The result of this research shows that early, dance Zapin Arab acts as a complementof ritual ceremony. The function of dance Zapin Arab, then, develops to be a personal entertainment in 1991and as an instrument of aesthetic presentation in 2008 along with the development of the form of Zapin Arabperformance. The development can be seen in the movement that is more varied and more dynamics, themore harmonious costume and the more magnificent stage. The development makes dance Zapin Arabmore interesting and more aesthetic. The development of its function and form is influenced by social,cultural, economic, and tourism factors.Keywords: dance Zapin Arab, development, function and form